Income inequalities: the rationale of demarcation amid growth and development - Gahlot, Bharat; Dubey, Akanksha (Journal of Management and Science, 2013)
In this paper we provide an analytical view of the effect of income inequality over economic development even in the charisma of continuous economic growth. In the beginning a detailed discussion has been done regarding the differences between economic growth and development.Ours is a developing economy with a continuous rise in GDP. However due to unequal distribution of income, the economy has not been able to witness economic development on an overall basis. An introduction is given regarding the HDI, the ultimate measure of economic development. This paper also proves the fact that economic development is possible only if there is equality in the distribution of income.In our study we have included a number of facts and figures to conclude that income equality is a precondition for economic development. At the end, few suggestions are given as to how we can overcome this problem and promote economic development.